Patient-Reported Goals in Tricuspid Regurgitation - Megan Coylewright, MD, MPH; Maurice Alston, DO; Suzanne V. Arnold, MD, MHA; Amanda Crowe, MA, MPH; Katherine Doermann Byrd, BA; Colleen K. McIlvennan, PhD, DNP, ANP; Rebecca T. Hahn, MD (JACC: Advances, 2025)
Background: New treatment options for symptomatic tricuspid regurgitation (TR) are now approved based on improvement in health status. Patient perspectives on goals of care for TR are poorly defined. Objectives: The objectives of this study are to understand the patient experience and gauge patient-defined knowledge gaps for TR, uncover patient goals for therapies, and define unmet needs, including key features for patient education. Methods: A patient forum using semistructured interview guides and preplanned activities was designed. Valvular heart disease physicians were engaged in patient recruitment. Qualitative analysis was used to generate themes and finalized with consensus between physicians, researchers, and a patient representative. Results: A 2-day patient forum, with inclusion of care partners, was held in Chattanooga, Tennessee, in November 2023. Ten patients and 9 care partners attended. Patients were older (mean age: 77 years [66-85]), more likely to be women (6/10, 60%) and self-identified as Black (3/10, 30%) or White (7/10, 70%). One-third of patients had some college education or higher (3/10, 30%), and half (5/10, 50%) had undergone a previous tricuspid valve repair or replacement. Qualitative analysis revealed the following 3 themes: 1) knowledge of TR was low; 2) TR severely affects independence and therefore care partners; and 3) earlier education and referral are needed. Conclusions: Patients with severe TR report loss of independence and reliance on care partners, with a need for earlier education on the disease process and treatment options. Further research is warranted on health care delivery interventions to facilitate early patient engagement on the management of symptomatic TR.